University Presidents and Politicians - Bissell, Claude T. (Canadian Journal of Higher Education, 1978)
It is customary to think of the ideal university president as being necessarily opposed to the methods and aims of the public politician. I f , as Thorstein Veblen argued, he adopts those methods and aims, he betrays the university and becomes, in effect, the head of a corporation or a minor state. It is the argument of this paper, however, that the president can lead and direct the University only if he accepts a political role, and strives to establish a high place for the university among public priorities. At the University of Toronto (and at other Canadian universities in varying degrees and in varying ways), the president was not able to play this political role until the great expansion of the 'sixties. Then, the need for long-range planning brought the presidents into the political arena. At the same time, internal stresses led to the creation of more representative governing bodies within the universities, and made the president a political figure who must strive to achieve a central alliance within the academic community.